Tantangan dan Solusi Dalam Menegelola Keuangan Sekolah Secara Efektif - Pri Sisilia Windy (CV. ITTC INDONESIA, 2025)
Sound financial management in schools plays a vital role in supporting the attainment of educational objectives. Nevertheless, numerous schools encounter obstacles such as limited financial resources, insufficient transparency, weak managerial capabilities, and inadequate oversight and accountability systems. These challenges often result in inefficient fund utilization, delays in executing programs, and risks of financial mismanagement. This article seeks to examine the primary issues in school financial management and offer implementable strategic solutions. The research is based on a literature review and policy analysis, emphasizing financial governance principles that incorporate transparency, accountability, and stakeholder involvement. The findings suggest that enhancing the financial planning and reporting skills of school leaders and treasurers, integrating digital systems for financial tracking, and encouraging active participation from school committees and communities in supervision are effective strategies to strengthen financial governance. By adopting these measures, schools can improve financial efficiency, accountability, and transparency, thereby fostering better educational outcomes.